1
$\begingroup$

Reading the book on Supergravity from Freedman & van Proeyen I was very bewildered by the so called cyclic identity of $\gamma$-matrices of the Clifford-algebra(eq. 3.67) important in string theory:

$$(\gamma_\mu)_{\alpha(\beta} (\gamma^\mu)_{\gamma\delta)} = 0 $$

(the round brackets indicate a symmetrisation operation on the matrix res. bispinor indices) which is according to the book for $D=3$ and $D=4$ a collorary of the Fierz identity:

$$(\gamma^\mu)_\alpha^{\;\beta} (\gamma_\mu)_\gamma^{\;\delta }=\frac{1}{2^m}\sum_A (-1)^{r_A} (D-2r_A) (\Gamma_A)_\alpha^{\;\delta} (\Gamma^A)_\gamma^{\;\beta} $$

where the $\Gamma_A$ the basis elements of the Clifford-algebra, $r_A$ their rank (in terms of $\gamma$-matrices, i.e. $r_A=0$ for $\Gamma_A=\mathbf{1},\, r_A=1$ for $\Gamma^A=\gamma^\mu$ and $r_A=2$ for $\Gamma^A = \gamma^{[\mu}\gamma^{\nu]}$ etc.) and $D$ the dimension of the considered space. $D$ is related to the integer $m$ either by $D=2m$ or $D=2m+1$.

I fear my capacities of proving that are rather limited, but at least I wanted to make a crosscheck. I know that in 3D (where the cyclic identity is supposed to hold) the $\gamma$-matrices can be represented by the Pauli-matrices $\gamma_0 = i\sigma_1$, $\gamma_1 = \sigma_2$ and $\gamma_2 = \sigma_3$. I put an imaginary $i$ as coefficient of $\sigma_1$ in order to make the 3D-$\gamma$ matrices Minkowski. Furthermore I assume that covariant and contravariant matrices are related with each other by $\gamma^{\mu} = \eta^{\mu\nu}\gamma_\nu$, i.e. by only a sign $\pm 1$. Then I write:

$$0=(\gamma_\mu)_{\alpha(\beta} (\gamma^\mu)_{\gamma\delta)}=-(\sigma_1)_{\alpha(\beta}(\sigma^1)_{\gamma\delta)}+(\sigma_2)_{\alpha(\beta}(\sigma^2)_{\gamma\delta)} + (\sigma_3)_{\alpha(\beta}(\sigma^3)_{\gamma\delta)}$$

Then I chose the simplest set of indices $\alpha=\beta=\gamma=\delta=1$ and consider that any symmetrisation on equal indices stays without effect:

$$-(\sigma_1)_{11}(\sigma^1)_{11}+(\sigma_2)_{11}(\sigma^2)_{11} + (\sigma_3)_{11}(\sigma^3)_{11}\neq 0$$

since $(\sigma^3)_{11} = 1$ whereas $(\sigma^1)_{11} = (\sigma^2)_{11} = 0$.

If this cyclic identity is right, then, I guess, I haven't understood something rather fundamental about it. I would very glad if somebody could demonstrate that I am wrong with the found counter-example and even more glad for a proof of it.

$\endgroup$
0
$\begingroup$

As the cyclic identity plays an important role in string theory (string and brane actions according to Freedman & van Proeyen (F&P)) I consider worth to post a "proof" of the cyclic identity, albeit in its certainly rather inelegant way. However, I am unaware of how/if it would work for $D>4$.

I had overlooked a detail in the way of lowering indices of $\gamma$-matrices that allowed me finally to proof the Fierz rearrangement cyclic identity at least in 3D. As F&P explain in their book for lowering indices of $\gamma$-matrices the charge conjugation matrix $C$ is applied that is also used for a scalar product of bispinors $\lambda$ and $\chi$: $\overline{\lambda} \chi:=\lambda^T C \chi$. So for $\gamma$-matrices one defines (I will use Latin indices for 4-vector indices and Greek letters for bispinor indices.):

$$\gamma^k_{\alpha\beta} = (\gamma_k)_\alpha^\gamma C_{\gamma\beta}\quad\quad (3.62) $$

Taking this into account the cyclic identity requires the following (index $\nu$ is not included in the symmetrisation operation):

$$0=(\gamma^k)_{\alpha(\beta} (\gamma_k)_{\gamma\delta)} = (\gamma^k)_\alpha^\mu C_{\mu(\beta}(\gamma_k)_\gamma^\nu C_{\nu\delta)}$$

According to F&P this is true for $D=3$ and $D=4$, so it is rather easy to check that for $D=3$ as the $\gamma$-matrices are only 2D. Actually I went through case by case using a 2D-representation of the $\gamma$-matrices from N.Lambert "Introduction to Supersymmetry" (Balkan Lectures 2011):

$$\gamma^0 = \left( \begin{array}{cc} 0 & 1 \\ -1 & 0 \end{array}\right)$$

$$\gamma^1 = \left( \begin{array}{cc} 0 & 1 \\ 1 & 0 \end{array}\right)$$

$$\gamma^2 = \left( \begin{array}{cc} 1 & 0 \\ 0 & -1 \end{array}\right)$$

The use of this representation implies a Minkowski-metric $\eta_{ik} = diag(-1,+1,+1)$. Finally, we assume that $C=\gamma^0$ given above, this $C$ indeed fulfills its definition equation: $(\gamma^k)^T = - C\gamma^k C^{-1}$.

My proof is rather primitive, as I checked it for the possible index permutations of 1 and 2: $(\beta,\gamma,\delta)=(111)$, $(112)$, $(221)$ and $(222)$. Furthermore there are 2 possibilities for $\alpha =1, 2$. The other permutations are due to the symmetrisation operation equivalent to one of the 4 cited cases. For instance for $(\beta,\gamma,\delta)=(111)$ we have for $\alpha=1$:

$$(\gamma^k)_{1(1} (\gamma_k)_{11)} = \eta_{ik}(\gamma^k)_1^2 C_{2(1}(\gamma^i)_1^2 C_{2 1)} = \eta_{ik}(\gamma^k)_1^2 C_{21}(\gamma^i)_1^2 C_{2 1}=-((\gamma^0)_1^2 )^2 + ((\gamma^1)_1^2 )^2 + ((\gamma^2)_1^2 )^2 = -1 + 1 + 0 =0$$

The case $(\beta,\gamma,\delta)=(111)$ seems to be particularly simple as all the indices are same, in particular the symmetrisation operation brackets can be omitted here as they have no effect. For $\alpha=2$ the evaluation is rather similar. Evidently I won't demonstrate it for all the cases, but I checked indeed for all the cases.

For $D=4$ the same style of proof would be really tedious, but actually more interesting than the pure $\gamma$-matrix relation is its application on Grassmann-bispinors $\lambda_\mu, (\mu=1,2,3)$(3.68):

$$\gamma_k \lambda_{[1}\overline{\lambda}_2 \gamma^k \lambda_{3]}=0. $$

This can actually be proven with the Fierz-relation (3.70). According to an addendum to chapter 3 of the F&P-book one starts off with $\gamma_k \lambda_{[1}\overline{\lambda}_{2]}\gamma^k \lambda_3$:

$$\gamma_k\lambda_{[1}\overline{\lambda}_{2]}\gamma^k \lambda_3 = -\frac{1}{4} \sum_A \gamma_k \Gamma^A\gamma^k \lambda_{3}\overline{\lambda}_{[2} \Gamma_A \lambda_{1]}$$

The sum runs over the basis of the Clifford-algebra. Due $\gamma$-matrix properties in D=4 in the term $\overline{\lambda}_{[2} \Gamma_A \lambda_{1]}$ only the cases $\Gamma_A = \gamma^k$ and $\gamma^{ik}$ need to be considered. Due to $\gamma_j \gamma^{ik}\gamma^j = (D-4)\gamma^{ik} =0$ we are only left with $\Gamma_A = \gamma^k$. Then we get using $\gamma_k \gamma^i\gamma^k =-2 \gamma^i$:

$$\gamma_k \lambda_{[1}\overline{\lambda}_{2]}\gamma^k \lambda_3 = -\frac{1}{4} (-2)\gamma^i\lambda_3\overline{\lambda}_{[2}\gamma_i \lambda_{1]}= -\frac{1}{2} \gamma^i\lambda_3\overline{\lambda}_{[1}\gamma_i \lambda_{2]}$$

Finally we get from this:

$$\gamma_k \lambda_{[1}\overline{\lambda}_{2]}\gamma^k \lambda_3 + \gamma_k \lambda_{[1}\overline{\lambda}_{2]}\gamma^k \lambda_3 + \gamma^k\lambda_3\overline{\lambda}_{[1}\gamma_k \lambda_{2]} =0$$

which can be cast in:

$$0=\gamma_k \lambda_{[1}\overline{\lambda}_{2]}\gamma^k \lambda_3 + \gamma_k \lambda_{[2}\overline{\lambda}_{3]}\gamma^k \lambda_1 + \gamma_k \lambda_{[3}\overline{\lambda}_{1]}\gamma^k \lambda_2 =3\gamma_k \lambda_{[1}\overline{\lambda}_2 \gamma^k \lambda_{3]}$$

QED.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.